The effect of supportive text message on the adherence to medication in depression: An experimental study - Aeen Mohammadi (Nursing Practice Today, 2016)
Background & Aim:Lack of adherence to prescribed medication is a main concern in medicine especially in chronic diseases. The aim of present study was to determine the effect of supportive text message on the adherence to treatment of depression.